Exploring the Motivation of Adolescent’ Participation in Physical Exercise: An Evolutionary Psychology Perspective - Fan Ke; Qijie Jiang (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
The extant scholarly discourse pertaining to adolescents' engagement in physical exercise predominantly comprises superficial observations and introductory comprehension, demonstrating a dearth of comprehensive analysis regarding the intricate psychological mechanisms at play. This investigation endeavours to delve into the foundational impetuses driving teenagers' participation in physical activity through the lens of evolutionary psychology theory. Furthermore, it aims to scrutinize the motivational processes and mechanisms by integrating the tenets of planned behavioural theory. A sample comprising 887 valid questionnaires was gathered from middle school, high school, and college students. Subsequently, a structural equation modelling approach, integrating regression and factor analysis, was employed to validate the initial model and associated hypotheses. This study utilized a quantitative research methodology along with a cross-sectional research design. Empirical investigation confirmed six hypotheses derived from the study. Notably, four evolutionary motives—namely, the inclination to avoid harm, mitigate disease risk, foster group affiliation, and pursue mate acquisition—exerted substantial direct effects on teenagers' intentions towards physical exercise. Moreover, these motives also demonstrated indirect impacts on teenagers' physical exercise intentions through subjective norms, attitudes, and perceived control over their physical exercise behaviour. Adolescents' engagement in physical exercise is shaped not solely by superficial factors and external stimuli but is also propelled by intrinsic motives rooted in evolutionary and natural selection mechanisms. An evolutionary perspective sheds light on the nuanced understanding of adolescents' physical exercise, consolidating disparate research on exercise motivation. Building upon this understanding, governmental bodies and educational institutions can devise novel policies and initiatives to foster physical activity among youth, facilitating the maintenance of robust physical health alongside educational pursuits.